IMPLEMENTASI PROGRAM KECAKAPAN KERJA (PKK) DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) â€œBUGENVILâ€ BAGI WARGA BINAAN LEMBAGA PEMASYARAKATAN KELAS II KALIANDA KABUPATEN LAMPUNG SELATAN - Triyono Triyono; Rosidah Rosidah; Hinfa Mosshananza (Jurnal Progress Administrasi Publik (JPAP), 2022)
By-Law No. 12 of 1995 concerning Correctional Services, PKBM Bugenvil's Work Skills Program (PKK) was established. The purpose of this research is to describe the problem of the process of implementing the Work Skills Program (PKK) PKBM Bugenvil which is less than optimal and has an impact on the built citizens. The research method used is qualitative. The results of the research that the implementation of PKK in PKBM "Bugenvil" has been carried out properly based on the content of existing policies and situations with the implementation model approach by Meriee. S. Grindle. In the Implementation of the Work Skills Program (PKK), there are inhibiting factors, namely; lack of government roles, tutors, managers, and policy advocates by local governments. Therefore, the local government is expected to pay special attention to the implementation of the PKBM Bugenvil Work Skills Program (PKK) through training, socialization, supervision, providing direction, motivation, advice, and improving communication with PKBM administrators. Â  Key Words: Implementation, PKBM